Campylobacter jejuni NCTC 11168 response to protamine sulfate - Hayek, Nabil (University of Ottawa (Canada), 2009)
Campylobacter jejuni is the principal cause of gastroenteritis worldwide. Contaminated chickens is the most important source of human infection by Campylobactor. In its hosts, C. jejuni colonizes the gastrointestinal tract despite the constitutive and induced secretion of cationic antimicrobial peptides (CAMPs). These peptides are a major component of the host's innate immune system and have been found to be effective against different bacterial species including Campylobacter . These observations suggest that Campylobacter has developed mechanisms to evade CAMPs. To test this hypothesis and identify genes presumably involved in adaptation and/or resistance to CAMPs, two approaches were pursued. In the first approach, the transcriptome profile of C. jejuni NCTC 11168 was analyzed upon exposure to increasing concentrations of protamine sulfate, which is a known antimicrobial peptide. In the second approach, a Campylobacter transposon mutant library was screened against two concentrations of protamine. The data obtained from both approaches revealed genes that could be important to overcome the effect of the studied antimicrobial agent and potentially other antimicrobial peptides. The transcriptome profile study unveiled the importance of two genes Cj1721c and Cj0355c, Cj1721c is an outer membrane protein with an unknown function, and Cj0355c, is an essential two-component system regulator. Phenotypic studies demonstrated that the Cj1721c knockout was more resistant to protamine, more motile, and had reduced biofilm-forming ability compared to the wild-type strain. In contrast, the strain that overexpresses Cj0355c was more sensitive to protamine and had greater biofilm-forming ability compared to the wild-type strain. Furthermore, it was attenuated in its ability to colonize the gastrointestinal tract of new born piglets. Moreover, transcriptome profiling of the strain that overexpresses Cj0335c in MH and MEM medium revealed potential pathways that could be regulated by this regulator. This observation suggests that membrane integrity could be sensed by a still unknown sensor and then the signal transferred to Cj0355c, which affects the expression of key genes that are involved in resistance to protamine sulfate. In summary, this study identifies previously uncharacterized genes (CJ1721c and Cj035c) that are involved in the resistance to protamine sulfate and potentially to other antimicrobial peptides. In addition, the performed transposon mutants library screening indicates that Campylobacter jejuni NCTC 11168 can intrinsically evade the effect of protamine sulfate. On the other hand, we showed that C. jeuni does not use the multidrug efflux pump (MATE) to resist the effect of protamine.
Keywords: Biology, Microbiology.